Exploiting S, N co-doped 3D hierarchical porous carbon with FeII–N4 moiety as an efficient cathode electrocatalyst for advanced Zn–air battery. (20th December 2020) - Yang, Zheng; Gao, Jingxia; Liu, Sa; Zhu, Ping; Huang, Shuangfei; Zeng, Dong; Zhao, Xinsheng; Wang, Guoxiang
Abstract: Transition-metal-coordination N-doped carbon (M–N–C) materials have been explored extensively as oxygen reduction reaction (ORR) electrocatlysts, owing to the low price, high conductivity and superior electrocatalytic property. Herein, an effective templating approach is developed for synthesizing high density of Fe II –N4 moiety dispersed in S, N-doped 3D hierarchical porous carbon (3DFe–S, N–C). Due to the high distribution of active sites, the large surface area and the abundant porosity, 3DFe–S, N–C displays a positive half-wave potential of 0.91 V and excellent ORR stability in alkaline medium. As demonstrated in cathode catalyst, 3DFe–S, N–C-based primary Zn–air battery (ZAB) can achieve a maximum power density of 160 mW cm −2 and specific energy density of 974 Wh kgZn −1 . In addition, the as-prepared catalyst also exhibits a potential application in solid-state and flexible ZAB.